Eco-friendly synthesis, characterization, and anticancer potential of iron oxide nanoparticles derived from Plectranthus amboinicus and Dorstenia foetida plant extracts - Adel A. M. Saeed; Eishah Mohammed Ali Mohsen; Abdul-Rahman Alawi Bin Yahia (Green Chemistry Letters and Reviews, 2025)
Iron oxide nanoparticles (IONPs) were synthesized using a green approach employing methanolic extracts of Plectranthus amboinicus and Dorstenia foetida. The color change from brown to black indicated IONP formation. Characterization included Ultraviolet–Visible Spectroscopy (characteristic peaks at 340 nm for P. amboinicus and ∼280 nm for D. foetida IONPs), Fourier Transform Infrared Spectroscopy (confirming hydroxyl groups and Fe-O bonds), X-ray Diffraction (crystallite sizes 26-30 nm), Proton Nuclear Magnetic Resonance Spectroscopy (suggesting phenolic involvement in reduction/stabilization), Energy-Dispersive X-ray Analysis (confirming iron and oxygen), and Field Emission Scanning Electron Microscopy (revealing diverse morphologies). The IONPs exhibited superior anticancer activity against THP-1 leukemia and Calu-3 lung cancer cells compared to parent extracts. P. amboinicus IONPs showed the highest efficacy (IC50: 25 μg/ml against THP-1, 34 μg/ml against Calu-3). Flow Cytometry revealed IONP-induced apoptosis. Analysis of Variance, t-tests, and Chi-square tests supported the enhanced anticancer potential of the green-synthesized IONPs. This eco-friendly synthesis offers a sustainable method for producing IONPs with promising therapeutic applications.